1994
DOI: 10.2337/diab.43.3.478
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Glucose-Enhanced Extracellular Matrix Accumulation in Rat Glomerular Mesangial Cells

Abstract: In view of the importance of mesangial extracellular matrix (ECM) accumulation in the pathogenesis of diabetic glomerulosclerosis, we investigated 1) the effects of high glucose on ECM production by rat glomerular mesangial cells in culture (study A) and 2) the mechanisms underlying these effects, particularly the role of high sugar levels irrespective of intracellular metabolism (study B1) and of excess glucose disposal via the polyol pathway and associated biochemical alterations (study B2). Cells were cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(39 citation statements)
references
References 72 publications
2
37
0
Order By: Relevance
“…AR inhibitor normalised not only the diabetic decrease in GSH concentrations, but also the diabetic increase in L/P ratios even in the presence of transgenic hAR. The increased L/P ratio of diabetic mice in our study is consistent with a report showing an increase in L/P ratios in rat glomerular mesangial cells exposed to glucose [41]. Because SDH-deficiency did not improve the diabetic increase in UAE, our study did not analyse GSH concentrations and L/P ratios in kidneys of SDH null or hAR-Tg:SDH null mice.…”
Section: Discussionsupporting
confidence: 90%
“…AR inhibitor normalised not only the diabetic decrease in GSH concentrations, but also the diabetic increase in L/P ratios even in the presence of transgenic hAR. The increased L/P ratio of diabetic mice in our study is consistent with a report showing an increase in L/P ratios in rat glomerular mesangial cells exposed to glucose [41]. Because SDH-deficiency did not improve the diabetic increase in UAE, our study did not analyse GSH concentrations and L/P ratios in kidneys of SDH null or hAR-Tg:SDH null mice.…”
Section: Discussionsupporting
confidence: 90%
“…Preliminary data showing unchanged rates of proliferation and apoptosis, unchanged patterns of matrix protein and cytokine production, and unchanged expression of mesangial cell-specific markers (Thy1.1, vimentin, and smooth muscle actin) indicated that these cells do not undergo detectable phenotypic changes at advanced passages in culture. Cells were seeded in 35-or 100-mm culture dishes (Falcon; Becton Dickinson, Lincoln Park, NJ) and grown to confluence in Dulbecco's modified Eagle's medium (Sigma, St. Louis, MO) supplemented with 17% fetal bovine serum and 2 mmol/l L-glutamine and antibiotics (all obtained from Flow Laboratories, Irvine, Scotland, U.K.) at 37掳C in a 95% air and a 5% CO 2 humidified atmosphere (3,21). Cells were exposed to one of the following 2 sets of conditions: 1) media containing high glucose (HG) levels (30 mmol/l) as compared with those containing iso-osmolar mannitol (M) (24.5 mmol/l + 5.5 mmol/l glucose) or media containing normal glucose (NG) levels (5.5 mmol/l) for 1-4 weeks, or 2) glycated bovine serum albumin with AGE formation (BSA-AGE) as compared with glycated BSA in which AGE formation was prevented by aminoguanidine (AM) (BSA-AM) or with nonglycated or native BSA, all previously prepared and either coated onto the culture dish or added to the culture media, for 4 days (3).…”
Section: Experimental Designmentioning
confidence: 99%
“…In vitro studies. Glomerular mesangial cells were isolated from human and rat kidneys and characterized as previously reported (3,21). Because the Gal-3 expression pattern was shown to vary with cell aging (i.e., increased basal and reduced serum-stimulated levels) (22), cells between the 3rd and the 15th passages (for human mesangial cells [HMCs]) and between the 5th and the 27th passages (for rat mesangial cells [RMCs]) were used in these experiments.…”
Section: Experimental Designmentioning
confidence: 99%
“…This difference in tissue response may reflect the constellation of cells present in myocardial capillaries (endothelial cells and pericytes) and glo-meruli, which contain epithelial cells in addition to endothelial and mesangial cells; previous studies from our laboratory have indicated that only the latter two cell types form type VI collagen, while all three synthesize type IV. Most previous investigations on the effect of glucose on collagen synthesis by cells in culture have focused on type IV and have found an approximately twofold increase in this protein, whether the elevated glucose was present during the entire growth period of endothelial [17,26] or mesangial [27][28][29] cells or when exposure of confluent glomerular epithelial, mesangial or endothelial cells was only for short periods of time [3,6]. The influence of elevated glucose on type VI collagen has previously been studied only with rat glomerular mesangial cells and in that system the extent of stimulation was similar for both types VI and IV collagens, even though marked differences were observed in other aspects of the response, with type VI reflecting more rapidly both increased and normalized glucose levels, and only type IV being enhanced by addition of the glucose metabolite pyruvate or by the presence of aldosterone or IGF-1 [3].…”
Section: Discussionmentioning
confidence: 99%